PENGARUH REGULASI USAHA, PENDIDIKAN KEWIRAUSAHAAN, DAN DUKUNGAN SOSIAL TERHADAP MINAT BERWIRAUSAHA DENGAN EFIKASI DIRI SEBAGAI VARIABEL MEDIASI PADA IBU PKK DI KABUPATEN JEPARA - Cakra, Mustofa; Hardian, Dafyar Eliadi; Mulyadi, Edi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study aims to determine the effect of business regulations, entrepreneurship education, and social support on entrepreneurial interest, with self-efficacy as a mediating variable among Family Welfare Movement (PKK) mothers in Jepara Regency. This study used a quantitative approach, collecting numerical data through questionnaires and analyzing it using statistical methods, involving a sample of 100 participants. Structural Equation Modeling (SEM) was used to validate the relationships and influences among the variables. The findings indicate that business regulations influence entrepreneurial interest. The T-statistic value was 3.427 > 1.967 with a significance value of 0.001 < 0.05. Entrepreneurship education also influenced entrepreneurial interest, with a T-statistic value of 2.794 > 1.967 with a significance value of 0.005 < 0.05. The social support variable has an influence on Entrepreneurial Interest, which is indicated by a T Statistic of 2.831 > 1.967 and a significance value of 0.005 < 0.05. The self-efficacy variable influences entrepreneurial interest, with a T Statistic of 2.542 > 1.967 and a significance value of 0.011 < 0.05. The business regulation variable influences self-efficacy, with a T Statistic of 3.128 > 1.967 and a significance value of 0.002 < 0.05. The entrepreneurship education variable influences self-efficacy, with a T Statistic of 2.988 > 1.967 and a significance value of 0.003 < 0.05. The social support variable influences self-efficacy, with a T Statistic of 2.961 > 1.967 and a significance value of 0.003 < 0.05. Meanwhile, mediationally, business regulations do not have a significant indirect effect on entrepreneurial interest through self-efficacy, with a T-statistic of 1.880 < 1.967 and a significance value of 0.061 > 0.05. Entrepreneurship education has an indirect effect on entrepreneurial interest through self-efficacy, with a T-statistic of 2.068 > 1.967 and a significance value of 0.039 < 0.05. Social support does not have an indirect effect on entrepreneurial interest through self-efficacy, with a T-statistic of 1.823 < 1.967 and a significance value of 0.069 > 0.05. Keywords: Business Regulations, Entrepreneurship Education, Social Support, Self-Efficacy, Entrepreneurial Interest.